2016
DOI: 10.1002/ajp.22624
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzee seed dispersal in a montane forest fragment in Rwanda

Abstract: Chimpanzees in Gishwati disperse a significant number of large seeds. Large-bodied seed dispersers, like chimpanzees, are particularly important in regenerating forest fragments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Generalization of Afrotropical frugivores might functionally compensate for the lower diversity of animal frugivores compared with the Neotropics. Interestingly, this trend towards a greater generalization in Afrotropical frugivores with a high fruit dependence was unrelated to body mass and, thus, is not a result of the generalized diet of large mammals only (Campos‐Arceiz & Blake, ; Chancellor et al, ), but fruit‐dependent animals in the Afrotropics appear to be more generalized in their fruit resource use regardless of body size. Our findings corroborate earlier studies that have also shown that the degree of frugivory is generally a more important functional trait than body mass in seed‐dispersal networks (Mello et al, ; Sebastián‐González, ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Generalization of Afrotropical frugivores might functionally compensate for the lower diversity of animal frugivores compared with the Neotropics. Interestingly, this trend towards a greater generalization in Afrotropical frugivores with a high fruit dependence was unrelated to body mass and, thus, is not a result of the generalized diet of large mammals only (Campos‐Arceiz & Blake, ; Chancellor et al, ), but fruit‐dependent animals in the Afrotropics appear to be more generalized in their fruit resource use regardless of body size. Our findings corroborate earlier studies that have also shown that the degree of frugivory is generally a more important functional trait than body mass in seed‐dispersal networks (Mello et al, ; Sebastián‐González, ).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, the higher diversity of fruit types in the Neotropics facilitates niche partitioning among Neotropical frugivores (Fleming et al, ) and could act as a mechanism that reinforces the high diversity of plants in Neotropical compared with Afrotropical forests (Terborgh et al, ). Another explanation for the difference between continents could be that the frugivorous megafauna, such as primates or large ungulates, have a generalized diet (Campos‐Arceiz & Blake, ; Chancellor, Rundus, & Nyandwi, ). The extinction of frugivorous megafauna from the Neotropical continent ca .…”
Section: Discussionmentioning
confidence: 99%
“…As with other disease-associated clostridia, sarcinae form environmentally stable spores 106 and may be ubiquitous in soil 79,99,107 , but environmental factors may contribute to germination of spores and overgrowth. Seasonal changes known to be important in chimpanzees, such as habitat use, diet (including exposure to plant or arthropod toxins), and physiological condition 108 , may increase infection risk at certain times of the year. Alternatively, "Ca.…”
Section: Amentioning
confidence: 99%
“…Outliers and overlap in this environmental continuum can likely be explained by anthropogenic influences: The dense forest outlier in the bottom left panel of Fig. 3 (i.e., Gishwati in Rwanda) likely fell into the savanna-mosaic side of the environmental continuum as this site represents a forest island amidst a human-dominated landscape and therefore has relatively low forest cover and Hansen tree cover (Chancellor et al 2012a;Chancellor et al 2017). Similarly, the two forest mosaic sites that fell closest to the chimpanzee researcher-classified savanna sites in Fig.…”
Section: Discussionmentioning
confidence: 99%